McArdle disease: a clinical review. Issue 11 (22nd September 2010) - Quinlivan, R; Buckley, J; James, M; Twist, A; Ball, S; Duno, M; Vissing, J; Bruno, C; Cassandrini, D; Roberts, M; Winer, J; Rose, M; et al.
Abstract : Methods: The clinical phenotype of 45 genetically confirmed McArdle patients is described. Results: In the majority of patients (84%), the onset of symptoms was from early childhood but diagnosis was frequently delayed until after 30 years of age. Not all patients could recognise a second wind although it was always seen with exercise assessment. A history of myoglobinuria was not universal and episodes of acute renal failure had occurred in a minority (11%). The condition does not appear to adversely affect pregnancy and childbirth. Clinical examination was normal in most patients, muscle hypertrophy was present in 24% and mild muscle wasting and weakness were seen only in patients over 40 years of age and was limited to shoulder girdle and axial muscles. The serum creatine kinase was elevated in all but one pregnant patient. Screening for the mutations pArg50X (R50X) and pGly205Ser (G205S) showed at least one mutated allele in 96% of Caucasian British patients, with an allele frequency of 77% for pArg50X in this population. A 12 min walking test to evaluate patients is described. Conclusion: The results demonstrated a wide spectrum of severity with the range of distance walked (195–1980 m); the mean distance walked was 512 m, suggesting significant functional impairment in most patients.